An Investigation Of Photonic Band Structure For Metallic Photonic Crystals - Low , Khee Lam (2011)

(untitled)
Photonic crystals are artificial periodic structures. Their unique properties are one of the most extensively studied topics in the past 20 years. Researchers believe that this structure can overcome the challenge that we are facing nowadays in the nano-optics related research field. In this thesis, the nature of photonic crystals has been investigated. One of the most important parameters that exhibits the characteristic or properties of photonic crystals is the photonic band structure.